A Task Analysis of Key Processes to Access an Exiled Part in Internal Family Systems. - Welch, Tim S.; White-VanBoxel, Jennifer; Timm, Tina M.; Blow, Adrian (American Journal of Family Therapy, 2026)
A discovery-oriented task analysis was conducted to identify and describe the process of accessing an exiled part, a key component in Internal Family Systems. After developing a rational model based on existing clinical literature and writing, 7 videos obtained from the model developer were analyzed and transcribed to identity the steps and processes associated with accessing an exiled part. We identified 5 steps and 11 processes which provide detailed information on the techniques used to access an exiled part. Our findings build on existing descriptions of this task and provide a more concrete detailed description of this process.